ChartStamp: Robust Chart Embedding for Real-World Applications - Fu, Jiayun; Zhu, Bin Benjamin; Zhang, Haidong; Zou, Yayi; Ge, Song; Cui, Weiwei; Wang, Yun; Zhang, Dongmei; Ma, Xiaojing; Jin, Hai (Proceedings of the 30th ACM International Conference on Multimedia (MM '22), 2022)
Deep learning-based image embedding methods are typically designed for natural images and may not work for chart images due to their homogeneous regions, which lack variations to hide data both robustly and imperceptibly. In this paper, we propose ChartStamp, the first chart embedding method that is robust to real-world printing and displaying (printed on paper and displayed on screen, respectively, and then captured with a camera) while maintaining a good perceptual quality. ChartStamp hides 100, 1,000, or 10,000 raw bits into a chart image, depending on the designated robustness to printing, displaying, or JPEG. To ensure perceptual quality, it introduces a new perceptual model to guide embedding to insensitive regions of a chart image and a smoothness loss to ensure smoothness of the embedding residual in homogeneous regions. ChartStamp applies a distortion layer approximating designated real-world manipulations to train a model robust to these manipulations. Our experimental evaluation indicates that ChartStamp achieves the robustness and embedding capacity on chart images similar to their state-of-the-art counterparts on natural images. Our user studies indicate that ChartStamp achieves better perceptual quality than existing robust chart embedding methods and that our perceptual model outperforms the existing perceptual model.